Infectious native aortic aneurysm with negative blood cultures: do not forget the pneumococcal urinary antigen test!. Issue 3 (26th January 2023) - Dubert, Marie; Derycke, Lucie; Bidaud, Anne‐Laure; Gibault, Laure; Le Pendu, Claire; Pogdlajen, Isabelle; Lebeaux, David
Abstract : Infectious native aortic aneurysm (INAA) are rare but life‐threatening infections. Early microbiological identification is crucial to initiate adequate therapy and decrease the peri‐operative risk, but can be challenging when blood cultures remain negative. We describe two cases of pneumococcal INAA with negative blood cultures, diagnosed in the with the pneumococcal urinary antigen test.